2005
DOI: 10.1038/sj.bjp.0706196
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, expression and pharmacological characterization of the canine cholecystokinin 1 receptor

Abstract: 1 The full-length, canine cholecystokinin 1 (CCK1) receptor was cloned from gallbladder tissue using RT-PCR with a combination of primers designed to interact with conserved regions of the human and rat CCK1 receptor, which also shared homology with the canine genomic sequence. . Furthermore, the selectivity of these compounds between canine CCK1 and CCK2 receptors was consistent with the selectivity between the human CCK1 and CCK2 receptors. 4 Two additional forms of the canine CCK1 receptor were identified d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…As far as we are aware, the mechanism of this ‘tachyphylaxis’ has not been established, however, there are a number of differences between JNJ‐26070109 and YF476. These include the observation that while YF476 has very high affinity for the human CCK 2 receptor, it is only ∼60‐fold selective over the related human CCK 1 receptor, whereas JNJ‐26070109 is >1200‐fold selective for the human CCK 2 over the CCK 1 receptor (Morton et al ., 2005a,b; 2011b). This may be of functional significance as gastrin/cholecystokinin dual knockout mice have a phenotype where acid secretion is similar to controls.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we are aware, the mechanism of this ‘tachyphylaxis’ has not been established, however, there are a number of differences between JNJ‐26070109 and YF476. These include the observation that while YF476 has very high affinity for the human CCK 2 receptor, it is only ∼60‐fold selective over the related human CCK 1 receptor, whereas JNJ‐26070109 is >1200‐fold selective for the human CCK 2 over the CCK 1 receptor (Morton et al ., 2005a,b; 2011b). This may be of functional significance as gastrin/cholecystokinin dual knockout mice have a phenotype where acid secretion is similar to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit CCK1R is 92% homologous (87% identity) to the rat CCK1R sequence (8,119). Canine gallbladder CCK1R is 89% identical to the human and 85% identical to the rat CCK1R (97). Different animal species share ϳ90% identity in their CCK1R amino acid sequence (102).…”
Section: Cck Receptor In Different Animal Speciesmentioning
confidence: 90%
“…At the time, however, the affinity of these antagonists to the canine CCK1 receptors had not been systematically evaluated and thus the actual selectivity was unknown. Recently, it was demonstrated that L-364,718 expresses about 60-fold increased affinity at the canine CCK1 over the canine CCK2 receptors by cloning the canine CCK1 receptor and subsequent pharmacological analysis of the CCK receptor ligands, and therefore can be considered CCK1 receptor-selective in dogs and humans (Morton et al, 2005).…”
Section: Role Of Cck and Cck Receptorsmentioning
confidence: 99%